Teachers’ Challenges in Teaching Reading Comprehension at Islamic Junior High School - Ridwan Hidayat; Ridha Ilma; Eko Saputra (Didascein : Journal of English Education, 2024)
There are many challenges teachers must go through in terms of developing reading comprehension and the benefits can be seen after the teacher implements them, education stakeholders. This study used a qualitative study with a case study research approach to identify teacher challenges in teaching reading comprehension. There were two English teachers from one of the Islamic junior high schools in Palembang which was chosen as the sample by using purposive sampling and the interview was the instrument to collect the data. Thematic analysis was used to analyze the data. The results showed that teachers faced several challenges in teaching reading comprehension, such as (1) challenges in teaching, (2) teaching method, (3) lack of understanding, (4) assessing students' abilities, (5) Students' lack of vocabulary mastery, (6) students' boredom, (7) mother tongue interference. It was hoped that English teachers might help students comprehend the meaning of a given text and choose reading materials that suit their reading level and interests.